Product Cost Calculation Methods in Construction - Dmitrenko, Alla; Lebedyk, Galyna; Nesterenko, Mykola (International Journal of Engineering and Technology, 2018)
The order of accounting and features of the methodology of cost expenditures at the concrete enterprises of the field was studied and it has been found out the fact that in the practical activity of the enterprise, they tend to apply the normative method of cost expenditures accounting. It has been conducted a detailed research of enterprises which use the normative method of cost expenditure accounting, and the calculation of the planned cost price. In addition, given advantages of the normative method of cost expenditure accounting have two functions: it provides the operational control over the production cost expenditures by accounting for cost expenditures under current norms and their changes and provides accurate calculation of the cost price of construction products.Â